Superior Semicircular Canal Dehiscence Syndrome - Steenerson, Kristen K.; Crane, Benjamin T.; Minor, Lloyd B. (Seminars in Neurology, 2020)
Superior canal dehiscence syndrome (SCDS) is a vestibular disorder caused by a pathologic third window into the labyrinth that can present with autophony, sound- or pressure-induced vertigo, and chronic disequilibrium among other vestibulocochlear symptoms. Careful history taking and examination in conjunction with appropriate diagnostic testing can accurately diagnose the syndrome. Key examination techniques include fixation-suppressed ocular motor examination investigating for sound- or pressure-induced eye movements in the plane of the semicircular canal. Audiometry, vestibular evoked myogenic potentials, and computed tomography confirm the diagnosis. Corrective surgical techniques can be curative, but many patients find their symptoms are not severe enough to undergo surgery. Although a primarily peripheral vestibular disorder, as first-line consultants for most dizziness complaints, neurologists will serve their patients well by understanding SCDS and its role in the differential diagnosis of vestibular disorders.
Keywords: superior canal dehiscence syndrome; superior semicircular canal; third window phenomenon; vestibular disorder